Cholangioscopy as a therapeutic alternative for the removal of biliary stents with proximal migration: case report - Arango Molano, Lázaro (2025)
Endoscopic biliary plastic stent placement is standard therapy for biliary obstruction secondary to benign and malignant diseases. Complications associated with its placement are low, but potentially dangerous for the patient, especially those associated with proximal migration of the stent in the bile duct, which requires additional manipulations of the bile duct for its extraction using standard methods through endoscopic retrograde cholangiopancreatography in most patients. We present the clinical case of a patient with proximal migration and impaction of a plastic biliary stent, which required the use of advanced endoscopic techniques through cholangioscopy for its extraction.